Abbreviated version of Penn State Worry Questionnaire for Chinese adolescents: Age, gender and longitudinal invariance - Xie, Shan-Shan; Xiao, Hui-Wen; Lin, Rong-Mao (Frontiers in Psychiatry, 2023)
The abbreviated version of Penn State Worry Questionnaire (PSWQ-A) has been widely used to assess worry. However, its measurement invariance has been not yet warranted. With a cross-sectional and a longitudinal sample of Chinese adolescents (N1 = 1,329, N2 = 408), this study examined age, gender, and longitudinal invariance of PSWQ-A. Results supported strict invariance, including configural, metric, scalar, and error level, across gender and age in the cross-sectional sample; strict longitudinal measurement invariance was also supported in the longitudinal sample. This study suggests the application of the PSWQ-A in measuring adolescent worry and a basis for comparisons of different populations and occasions for worry.